(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A series of phylogenetic analyses was undertaken using 144 characters from macropterous males of 94 taxa in 16 families of non-margarodid Coccoidea, with Ortheziidae as outgroup. Tue results are presented and discussed. Although there is good bootstrap support for most of the traditional family groupings, support for inter-family relationships is poor or absent. However, in almost all trees, the Stictococcidae were sister to the Beesoniidae, the Conchaspididae were sister to the Diaspididae and the Aclerdidae were sister to the Coccidae, although there is no bootstrap support for this last grouping. The Pseudococcidae and Eriococcidae were never monophyletic. The analyses also suggested that Puto and Phenacoleachia might be closely related.